(untitled) (Nonconventional Technologies Review, 2021)
Nonconventional Technologies, and therefore dimensional processing technologies, are generally defined as those methods and technological procedures which are still in the phase of elucidation and the command of constructive solutions, their intrinsic technological possibilities and condition of practice is still in an incipient or a development phase. As well, the dialectic character of these delimitations is generally accepted, due to the permanent evolution of this field towards that of conventional technologies, determined by the scientific and technological achievements.